Pengaruh Intelegence Quotient (IQ), Emotional Quotient (EQ) dan Spiritual Quotient (SQ) Terhadap Prestasi Belajar Mata Kuliah Pendidikan Pancasila pada Taruna Diploma III Manajemen Transportasi Udara Angkatan III-A di Politeknik Penerbangan Surabaya - Sutar Sutar; Didi Hariyanto (Jurnal Penelitian)
Intelligence quotient (IQ), Emotional quotient (EQ) and Spiritual Quotient (SQ) are forms of intelligence that must be actualized, guided and developed through the learning process to arrive at the level of balance, so that a person (learners) adapting himself to his environment in certain circumstances. The person who is able to deal with and overcome any problems that arise in front of him is a person who has the intelligence of life, all of which is a duty for educators to learners in the learning process. Result of F Test calculation done with aid of SPSS program got F value counted 102,369. with a significance value of 0.000. this value is smaller than a = 0,05,so the mean simultaneously independent variables consisting of variables Quotient Quotient (IQ) (X1), Emotional Quotient (EQ) (X2) and Spiritual Quotient (SQ) (X3) affect the variable tied Learning Achievement (Y) pancasila education courses cadet of diploma III air transportation management at Aviation Polytechnic of Surabaya. From the calculation result, it is known that the variable of Integral Quotient (IQ) (X1) has the t-count value of 8.160 and the significance value is 0,000, the Emotional Quotient (EQ) (X2) has the t-count value of 10.772 and the significance value is 0.000 Spiritual variable Quotient (SQ) (X3) has a t-count value of 11.886 and its significance value is 0,000. This significance value is smaller than a = 0,05, so it means partially independent variables consisting of Intelegence Quotient (IQ) (X1), Emotional Quotient (EQ) (X2) and Spiritual Quotient (SQ) (X3) have an effect on dependent variable that is Learning Achievement (Y) pancasila education courses cadet of diploma III air transportation management at Aviation Polytechnic of Surabaya.